A new genus and species of the family Isididae (Coelenterata: Octocorallia) from a CMAR Biodiversity study, and a discussion on the subfamilial placement of some nominal isidid genera - Alderslade, Philip; Mcfadden, Catherine S. (Zootaxa, 2012)
We describe a new abyssal genus and species of bamboo coral (family Isididae) with some markedly unusual characteris-tics, collected from a depth of just over 2000 m off southern Tasmania. Jasonisis thresheri n. gen., n. sp. possesses a fleshytegument that contains nematocysts, tubular axial internodes that are internally partitioned, scale-shaped sclerites thathave a morphology not recorded before for octocorals, and polyps that lack thorny rods or double stars in the pharynx.Molecular data place Jasonisis n. gen. in the subfamily Keratoisidinae whose definition is altered to incorporate the un-usual characters. We also report some comparative observations on the internal structure of the axial internodes of theisidid genera Keratoisis Wright, 1869, Lepidisis Verrill, 1883 and Isidella Gray, 1857, and we alter the definition of thesubfamily Mopseinae to allow the inclusion of the genera Tenuisis, Echinisis sensu Bayer & Stefani 1987 and Sclerisis sensu Bayer & Stefani 1987.